ELEVATED CIRCULATING ENDOTHELIN-1 AND OXIDATIVE STRESS AS POTENTIAL BIOMARKERS FOR PREECLAMPSIA IN WOMEN FROM TAMILNADU: A CASE CONTROL STUDY. - P.Bagavathiammal; P. M. Sasikala; R.Menaha; Revathi.A; Periasamy , Panneerselvam; Gunasekaran, Dr. Sasikala (Student's Journal of Health Research Africa, 2025)
Background Preeclampsia (PE) is a hypertensive disorder of pregnancy characterized by endothelial dysfunction and oxidative stress, contributing to maternal and fetal morbidity. Endothelin-1 (ET-1), a potent vasoconstrictor, has been implicated in the pathogenesis of PE. Objective: This study aimed to evaluate ET-1 and oxidative stress markers as potential biomarkers for preeclampsia in pregnant women from Erode, Tamil Nadu. Methods A prospective case-control study was conducted at Government Erode Medical College Hospital, involving 86 pregnant women. Participants were categorized into preeclamptic cases (n = 46) and normotensive controls (n = 40). Serum levels of ET-1, total oxidative status (TOS), total antioxidative status (TAS), and oxidative stress index (OSI) were measured. Independent t-tests and Pearson’s correlation were performed to evaluate group differences and associations. Results The preeclamptic group had significantly elevated ET-1 (1.39 ± 1.31 pg/ml vs. 1.27 ± 0.285 pg/ml, p = 0.023), higher TOS (119.44 ± 6.48 µmol/L vs. 112.88 ± 3.23 µmol/L, p = 0.034), lower TAS (1.04 ± 0.259 mmol/L vs. 1.47 ± 0.388 mmol/L, p = 0.001), and higher OSI (1.44 ± 1.29 vs. 0.867 ± 0.421, p < 0.001). Demographic variables such as mean age (24.01 ± 3.43 vs. 22.64 ± 2.16 years), gravidity, and gestational age (33.1 ± 4 vs. 32 ± 4.3 weeks) showed no significant differences, confirming matched groups. Pearson’s correlation revealed a weak, non-significant association between ET-1 and OSI. Conclusion Preeclampsia is associated with elevated oxidative stress and ET-1 levels, supporting their role as potential biomarkers. These findings may aid in early diagnosis and improved clinical monitoring of PE. Recommendations Future multi-center studies with larger cohorts and longitudinal follow-up are recommended to confirm these findings, explore causal mechanisms, and evaluate the utility of ET-1 and oxidative stress markers for risk stratification and therapeutic interventions in high-risk pregnancies.